Fondant fumble - McKinlay, Jenn (McKinlay, Jenn. Cupcake bakery mystery., 2024)
Professional football players Keogh Graham and Tyler Matthews want to open a Fairy Tale Cupcakes franchise. They're spending the off-season in Scottsdale working in Mel's bakery, learning about the business and how to bake show-stopping cupcakes. The popular athletes bring a boom of customers to the store as football fans flock to see the friends mixing batter and piping icing. Everyone's excited the athletes are pursuing their dream of owning a bakery-except for those who fear the players will ditch football for fondant and retire early from professional sports. The angry naysayers include their team owner and Keogh's sports agent, along with some very vocal fans. When the owner of their team, the Arizona Scorpions, is found dead on the floor of their new bakery following an argument with Keogh, the pros become prime suspects. As the investigation heats up, Mel and the rest of the cupcake bakery crew must step up and prove their franchise owners are innocent before it's game-over for the new bakers.--